Blastocystis subtypes in irritable bowel syndrome and inflammatory bowel disease in Ankara, Turkey - Funda Dogruman-Al; Semra Kustimur; Hisao Yoshikawa; Candan Tuncer; Zahide Simsek; Mehmet Tanyuksel; Engin Araz; Kenneth Boorom (Memorias do Instituto Oswaldo Cruz, 2009)
Blastocystis infection has been reported to be associated with irritable bowel syndrome (IBS), inflammatory bowel disease (IBD) and chronic diarrhoea. The availability of data on the subtypes of Blastocystis found in these patient groups would be of interest in understanding the significance of Blastocystis infection in chronic illness. In this study, we identify Blastocystis subtypes found in patients presenting with IBS, IBD, chronic diarrhoea and asymptomatic patients in Ankara, Turkey. Blastocystis was detected in 11 symptomatic patients by microscopy and 19 by stool culture. Stool culture was more sensitive than microscopy in identifying Blastocystis. Using standard nomenclature adopted in 2007, Blastocystis sp. subtype 3 was the most common in all groups, followed by Blastocystis sp. subtype 2. Identical subtypes of Blastocystis are found in patients with IBS, IBD and chronic diarrhoea. These particular subtypes show low host specificity and are carried by humans and some farm animals. The subtypes of Blastocystis that are commonly found in rodents and certain wild birds were not found in these patients. We suggest a model in which the severity of enteric protozoan infection may be mediated by host factors.